Novel hybrids of fluconazole and furanones: design, synthesis and antifungal activity - Borate, Hanumant B.; Sawargave, Sangmeshwer P.; Chavan, Subhash P.; Chandavarkar, Mohan A.; Iyer, Ramki; Tawte, Amit; Rao, Deepali; Deore, Jaydeep V.; Kudale, Ananada S.; Mahajan, Pankaj S.; Kangire, Gopinath S. (Bioorganic & Medicinal Chemistry Letters, 2011)
During our efforts to develop new antifungal agents, a number of hybrid molecules containing furanones and fluconazole pharmacophores were designed and synthesized. The new chemical entities thus synthesized were tested for their potential as antifungal agents against various fungal strains and it was observed that the compounds with general structure 7 were potent inhibitors of Candida albicans ATCC 24433, Candida glabrata ATCC 90030, Candida tropicalis ATCC 750 and Candida neoformans ATCC 34664 while the fluconazole analogues 12 exhibited antifungal activity against Candida albicans ATCC 24433 and Candida glabrata ATCC 90030. The structure-activity relationship for these compounds is discussed. The synthetic strategies used in the present work have potential to prepare a large number of compounds for further refinement of structures to obtain molecules suitable for development as antifungal drugs. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; Fluconazole; Furanones

One-step synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines and their use in the synthesis of highly functionalized 2,3,5,6,7-and 2,3,4,5,7-substituted indoles - Sawargave, Sangmeshwer P.; Kudale, Ananada S.; Deore, Jaydeep V.; Bhosale, Dattatry S.; Divse, Jaisingh M.; Chavan, Subhash P.; Borate, Hanumant B. (Tetrahedron Letters, 2011)
A three-component, one-step method for the synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines involving reaction of alkyl aldehyde, malononitrile and aryl aldehyde in presence of morpholine is reported. Highly functionalized 2,3,5,6,7- and 2,3,4,5,7-substituted indoles were prepared from these dicyanoanilines by reaction with ethyl bromoacetate. These substituted dicyanoanilines and indoles have a potential to be converted into various other compounds taking advantage of various functional groups present in these molecules. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Dicyanoanilines; indoles; Malononitrile

Synthesis of substituted 2,6-dicyanoanilines and related compounds. a review - Borate, Hanumant B.; Kudale, Ananada S.; Agalave, Sandip G. (Organic Preparations and Procedures International, 2012)

One-step method for the synthesis of aryl olefins from aryl aldehydes and aliphatic aldehydes - Borate, Hanumant B.; Gaikwad, Supriya H.; Kudale, Ananada S.; Chavan, Subhash P.; Pharande, Shrikant G.; Wagh, Vitthal D.; Sawant, Vikram S. (Tetrahedron Letters, 2013)
A conceptually new one-step reaction affording unexpected aryl olefinic product from aromatic aldehyde, aliphatic aldehyde and malononitrile in the presence of acetic acid-ammonium acetate under mild reaction conditions without using any metal catalyst is reported. This novel reaction was used to prepare a number of substituted aryl olefins including new molecules. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Aliphatic aldehyde; Aromatic aldehyde; Aryl olefin; Dicyanoaniline; Malononitrile

Synthesis of biphasic nanomaterials based on ZnO and SnO2: application towards photocatalytic degradation of acid red dye - Kudale, Ananada S.; Kamble, Santosh B.; Gore, Anil H.; Pisal, Mahesh M.; Salokhe, Anil T.; Kolekar, Govind B.; Helavi, Vasant B. (Nano-Structures & Nano-Objects, 2019)
Zn2SnO4/SnO2 and ZnO/SnO2 biphasic nanocatalysts have been synthesized by a facile solvothermal method using ethylene glycol (EG) as solvent in three different ways maintaining the pH of the solution at either 3 or 9 followed by calcination at 700 °C. The nanocatalysts are characterized by different techniques to investigate their structure, composition, morphology and optical properties. The XRD results indicate the formation of pristine biphasic composites. The UV-absorbance and photoluminescence spectra confirms the formation of biphasic composites as well as presence of large number of defects in the prepared nanocatalysts. The biphasic nanocomposites possess better photocatalytic activity towards the degradation of Acid Red-183 (AR-183) dye than pristine SnO2 and ZnO nanoparticles. This is mainly due to better charge separation, minimal recombination rate of charge carriers and defect-riched structures of nanocatalysts.